Sorghum, germinated millet and chia cookies: development, chemical composition and sensory analysis - da Silva Fonte Bôa, Gabriela; Pereira da Silva, Bárbara; de Souza Dantas, Maria Inês; Ladeira Mendes Duarte, Fátima; Stampini Duarte Martino, Hercia; Lima Binoti, Mirella (Archivos Latinoamericanos de Nutrición (ALAN), 2022)
The objective of this work was to develop cookies using sorghum, germinated millet and chia flours. Four formulations (F) were used: F-sorghum (100% sorghum flour); F-Sorghum + chia (50% sorghum flour and 50% chia flour), F-millet (100% millet flour) and F-millet + chia (50% millet flour and 50% chia flour). The germinated millet flour was submitted to microbiological analysis. All cookies were evaluated in relation to chemical and sensory analyses, according to AOAC and hedonic nine-point scale, respectively. The statistical analysis was performed by the variance analysis and Tukey test at 5% probability. The F-millet formulation showed the least humidity content (4.59 ± 0.25g/100g), while chia containing cookies showed lesser concentrations of carbohydrates (F-sorghum + chia: 44.35 ± 4.34g/100g and F-millet + chia: 41.03 ± 1.40g/100g) and higher ash content (F-sorghum + chia: 3.80 ± 0.02g/100g and F-millet + chia: 3.42 ± 0.24g/100g) and of protein (F-sorghum + chia: 15.38 ± 0.44 g/100g and F-millet + chia: 18.06 ± 0.53 g/100g). The caloric value and the lipids content did not differ among formulations. The sensory analysis had 57 evaluators. The cookies produced with chia and germinated millet had higher rates for flavor, texture and general impression. In general, all tested biscuits had good sensory acceptance and nutritional quality being an alternative to increase the consumption of bioactive compounds and antioxidants. El objetivo fue desarrollar galletas utilizando harina de sorgo, mijo germinado y chía. Se utilizaron cuatro formulaciones (F): F-sorgo (100% harina de sorgo); Sorgo F + chía (50% harina de sorgo y 50% harina de chía), mijo F (100% harina de mijo) y mijo F + chía (50% harina de mijo y 50% harina de chía). La harina de mijo germinada se sometió a análisis microbiológico. Las galletas fueron sometidas a análisis químico y sensorial, según la AOAC y una escala hedónica de nueve puntos, respectivamente. El análisis estadístico se realizó mediante análisis de varianza y prueba de Tukey al 5% de probabilidad. La formulación F-mijo tuvo menor contenido de humedad (4,59 ± 0,25 g/100g), mientras que las galletas que contenían chía tuvieron concentraciones más bajas de carbohidratos (F-sorgo + chía: 44,35 ± 4,34 g/100g y F-mijo + chía: 41,03 ± 1,40 g / 100g), mayor contenido de cenizas (F-sorgo + chía: 3,80 ± 0,02 g/100g y F-mijo + chía: 3,42 ± 0,24 g/100g) y proteínas (F-sorgo + chía: 15,38 ± 0,44 g/100g y F mijo + chía: 18,06 ± 0,53 g/100g). El valor calórico y el contenido de lípidos no difirieron entre las formulaciones. El análisis sensorial contó con 57 evaluadores. Las galletas producidas con chía y mijo germinado tenían notas más altas de sabor, textura e impresión general. Las galletas testadas tuvieron buena aceptación sensorial y calidad nutricional, siendo una alternativa para incrementar el consumo de compuestos bioactivos y antioxidantes.